PENGARUH MOTIVASI KERJA DAN PELATIHAN KERJA TERHADAP KINERJA PEGAWAI BADAN KEUANGAN DAERAH KABUPATEN AGAM PROVINSI SUMATERA BARAT - Adid, Saputra Junimas; Sri, Indarti; Rosnelly, Roesdi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to knowing the influences of work motivation and job training on the performance of employees of the Regional Finance Agency of Agam Regency, West Sumatra. The population in this study included all Civil Servants (CSE) at the Regional Finance Agency of Agam Regency, West Sumatra, the total are 45 people. While the sample in this study includes the all of population. Primary data were collected using a questionnaire as an instrument for research results, to test the hypothesis in this study using multiple linear regression analysis with the help of the SPSS program. The sampling technique chosen was the saturated sampling method (the entire population was sampled, namely 45 employees at the Regional Finance Agency of Agam Regency, West Sumatra). The results of this study show that: 1) There is a positive and significant influence between work motivation on the performance of the employees in the Regional Finance Agency in Agam Regency, West Sumatra, 2) There is a positive and significant influence between job training on the performance of employees in the Regional Finance Agency of Agam Regency, West Sumatra. , 3) There is a positive and significant influence between work motivation and job training together on the performance of the employees of the Regional Finance Agency of Agam Regency, West Sumatera.Keywords : Work Motivation, Job Training, Employee Performance